2009
DOI: 10.4314/bjpm.v11i1.48828
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus – A Review Of Current Concepts In Management

Abstract: Tetanus is a vaccinepreventable disease that yearly causes a total of 309,000 deaths. Reports showed up to 1 million cases annually, mostly in underdeveloped countries. Clostridium tetani, the causative organism, is widespread in the faeces of domestic animals and humans, while spores of C. tetani are abundant in soil and in the environment surrounding the habitation of humans and animals. In developing countries, mortality rates are as high as 28 per 100,000; in North America the rate is less than 0.1 per 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 11 publications
(2 reference statements)
0
24
0
5
Order By: Relevance
“…Simply because they are young adults who are part of the population economically active and and at higher risk of injury. Regarding sex again, the higher proportion of men can be explained by the fact that men are more active handicrafts and exposed to injury and are susceptible to infection, and women are immune due to routine vaccination during pregnancy [4, 15]. Overcrowding, lack of hygiene, ignorance and poor living conditions can explain why the majority of patients are common residents of the largest and most populated and urbanized cities of Lubumbashi: Joint Appendix, Kampemba and Kenya.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simply because they are young adults who are part of the population economically active and and at higher risk of injury. Regarding sex again, the higher proportion of men can be explained by the fact that men are more active handicrafts and exposed to injury and are susceptible to infection, and women are immune due to routine vaccination during pregnancy [4, 15]. Overcrowding, lack of hygiene, ignorance and poor living conditions can explain why the majority of patients are common residents of the largest and most populated and urbanized cities of Lubumbashi: Joint Appendix, Kampemba and Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…The disease has become rare in developed countries mainly due to vaccination programs childhood to adulthood as well as measures of sterilization and aseptic technique [4, 8, 9]. Even in those countries when it is diagnosed, it remains a serious and deadly disease despite the progress of medicine and adequate resuscitation [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A facility-based study reported that though the disease had the (16,7.1%) among all diagnoses but mortality (62.5%) was one of the highest [27] (Table 1). In Nigeria, tetanus mortality rate varies from 38% to 60%, depending on the infrastructure facilities and personnel at the reporting center [28]. Neonatal tetanus (NNT) is a significant cause of death among babies in the first 28 days of life [29].…”
Section: Tetanusmentioning
confidence: 99%
“…Among the 11 cases of inhalation anthrax linked to the 2001 anthrax letter attacks in the United States, five were fatal despite aggressive medical care, including antibiotic therapy (11,12). Antibody-based antitoxin therapy, which has a long history of successful use as a medical countermeasure for bacterial toxins, such as tetanus (13,14) and botulinum (15), could serve as adjunct therapy for toxemic patients.…”
mentioning
confidence: 99%